River ice and water temperature prediction on the Danube - Liptay, Zoltán Árpád; Czigány, Szabolcs; Pirkhoffer, Ervin (Hungarian Geographical Bulletin, 2021)
This paper presents a modification of the theory of weighted mean temperatures for rivers. Rodhe, B. (1952) assumed the dominance of sensible heat transfer on ice formation. We aimed to improve the method for the evaluation of ice and water temperature based on a relatively low number of inputs. We further developed the model by introducing the effect of pre-existing ice, hence increasing the accuracy of the model on the timing of ice disappearance. Prediction accuracy of ±1 day was reached for the timing of the appearance of ice.Additional outputs have also been added to the model, including the termination of ice and the prediction of water temperature. The temperature calculation had a coefficient of determination of 95 percent, and a root mean square error of 1.33 °C during the calibration period without the use of observed water temperatures. The validation was carried out in a forecasting situation, and the results were compared to the energy balance.